PERAN REMAJA MASJID DALAM MENINGKATKAN NILAI-NILAIPENDIDIKAN AKHLAK PADA ANAK USIA 10-12 TAHUN MELALUI KEGIATAN TAMAN PENDIDIKAN AL-QUR’AN (TPQ) DI DESA TEBING BATU KECAMATAN SEBAWI KABUPATEN SAMBAS TAHUN 2022/2023 - Siti Nurhaliza; Parni Parni; Hadisa Putri (Adisam Publisher, 2025)
The purpose of this study is to reveal about first, knowing the morals of children aged 10-12 years in Tebing Batu Village, Sebawi District, Sambas Regency in 2022/2023. Second, knowing the form of mosque youth activities in improving moral education values through the activities of the Qur'an Education Park (TPQ) in Tebing Batu Village, Sebawi District, Sambas Regency in 2022/2023. Third, knowing the obstacles faced by mosque teenagers in improving the values of moral education for children aged 10-12 years through the Al-Qur'an Education Park (TPQ) activity in Tebing Batu Village, Sebawi District, Sambas Regency in 2022/2023. This study uses qualitative approach and phenomenological type of research. Data collection techniques use interviews, observation, and documentation. While data analysis techniques used data reduction, data presentation, verification and conclusions. Then the data validity checking techniques used are triangulation techniques and member checks. The results showed that; 1) The morals of children aged 10-12 years who take part in TPQ at the beginning of the students participating in TPQ do need to be guided with a more intensive approach as evidenced by what has been explained by the students and mosque teenagers, but over time, now the morals of students have begun to change towards good student morals. 2) The form of mosque youth activities to improve moral education values through TPQ activities are: cleaning the mosque together, Doing Asr prayers before returning from TPQ, giving group assignments so that they can help and respect each other, before returning home the students must line up neatly to shake hands, give a role model from a teacher which can be emulated by the students, Always warn of good things that students must apply in everyday life. 3) The obstacles of mosque teenagers in improving the values of moral education in children aged 10-12 years are: facilities and infrastructure, namely no study table and only one blackboard which results in ineflective learning because they have to take turns using it, the absence of learning modules that make learning irregular, and when the weather does not support students it is difficult to go to the mosque.